PENGEMBANGAN MODEL E–DEMOKRASI LOKAL MELALUI RADIO (Studi Pada Program Lang-lang Kota Radio Mayangkara FM) (Profetik: Jurnal Komunikasi, 2020)
The new model of developing electronic democracy through e-democracy makes local democracy very dynamic. The level of public trust in radio is very high with an indicator of the number of community members who voluntarily inform all incidents in Blitar City and Regency. This new concept in the framework of radio journalism is referred to as citizen journalism. This study intends to develop a tripartite model of local democracy between the information giver (complainant), the handling agency (the agency complained) and the media (radio) as a bridge in solving the problem. So far the research method used is using qualitative methods with emphasis on participatory aspects. Radio owners, program directors, reporters and listeners who complain are the core informants in this study. The sampling technique used was purposive sampling using data or source triangulation and theory triangulation as a test tool. The results of this study are in the form of the city langlang program as a forum for public discussion on air in the form of complainants reporting their problems to the radio through sms, telephone, e-mail and social media. The model developed is not only on air but also off water, so that complainants can communicate with related parties via the Mayangkara FM radio bridge.